Inventarisasi Tumbuhan Obat Di Desa Golo Ketak Kecamatan Boleng Kabupaten Manggarai Barat, NTT - Hastuti Hastuti; Herlina Herlina; Rofina Susanti Amis (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2022)
Indonesia is a country with enormous natural wealth, including a wealth of plant species and a diversity of tribes that have local wisdom in the form of traditional medicine traditions. This study aims to: (1) determine the types of medicinal plants; (2) Knowing the plant organs used for treatment; (3) Knowing the process of processing medicinal plants and how to use the ingredients. The research method used is descriptive method and data collection techniques are carried out through observation, interviews, exploration, collection and documentation. The research data were analyzed descriptively and tabulated in tabular form. The results showed: (1) there were 13 species of medicinal plants in Golo Ketak Village, Boleng District, West Manggarai Regency, (2) parts of the plant organs used to treat the roots/rhizomes/tubers, stems, leaves and fruits; (3) the me thod of processing medicinal plants is by boiling, grating, pounding and smearing Indonesia is a country with enormous natural wealth. This includes the richness of plant species and tribes. Every tribe in Indonesia has local wisdom in the form of traditional medicine. This research is an inventory study of medicinal plants conducted in Gelo Ketak Village, Boleng District, West Manggarai Regency, NTT. This study aims to: (1) determine the types of medicinal plants; (2) Knowing the plant organs used for treatment; (3) Knowing the process of processing medicinal plants and how to use the ingredients. The method used is a descriptive method. Data collection techniques were carried using observation, interviews, exploration, collection and documentation. The research data were analyzed descriptively and made in tabular form. The results showed: (1) there were 13 species of medicinal plants in Golo Ketak Village, Boleng District, West Manggarai Regency, (2) parts of the plant organs used to treat the roots/rhizomes/tubers, stems, leaves and fruits; (3) the method of processing medicinal plants is by boiling, grating, pounding and smearing.